Kepatuhan Penggunaan APD pada Petani : Systematic Review - Anita Camillia; Fitria Saftarina; Wiwi Febriana (Malahayati Nursing Journal, 2025)
ABSTRACT Farmers are one type of job that requires great physical strength and is exposed to many risks of work accidents and health hazards. One effort to prevent work accidents and occupational diseases is to use Personal Protective Equipment (PPE). However, awareness of the use of PPE among farmers is still low. The use of PPE for farmers certainly requires an assessment related to worker compliance in using PPE when working. To determine the factors of PPE compliance among farmers. The research method used is literature review. Data collection using Google Scholar, Science Direct, Cochrane, and Pubmed internet searches with the keywords "compliance" AND "farmer PPE compliance," farmers PPE compliance, and farmers PPE factors. The articles used are articles published in 2019-2024. 683 articles were obtained. Then, after screening based on inclusion criteria, the author obtained 23 articles to be reviewed. There are many farmers who do not use complete PPE. Factors that influence the use of PPE in farmers include knowledge, attitude, age, length of service, education, supervision, training, support, and availability of PPE. Keywords: Personal Protective Equipment, PPE, Compliance, Farmers ABSTRAK Petani merupakan salah satu jenis pekerjaan yang membutuhkan tenaga fisik yang besar dan banyak terpapar risiko kecelakaan kerja dan bahaya kesehatan. Salah satu upaya pencegahan kecelakaan kerja dan penyakit akibat kerja adalah dengan menggunakan alat pelindung diri (APD). Namun, kesadaran penggunaan APD di kalangan petani masih rendah. Penggunaan APD bagi petani tentunya perlu dilakukan pengkajian terkait kepatuhan pekerja dalam menggunakan APD saat bekerja. Untuk mengetahui faktor-faktor kepatuhan APD pada petani. Metode penelitian yang digunakan adalah Literature Review. Pengumpulan data menggunakan pencarian internet Google Scholar, Science direct, Cochrane, dan Pubmed dengan kata kunci "kepatuhan" AND "APD petani", farmers PPE compliance, dan farmers PPE factors. Artikel yang digunakan ialah artikel yang diterbitkan tahun 2019-2024. Didapatkan 683 artikel. Kemudian setelah dilakukan skrining berdasarkan kriteria inklusi, penulis mendapatkan 23 artikel untuk dilakukan review. Terdapat banyak petani yang tidak menggunakan APD lengkap. Faktor yang memengaruhi penggunaan APD pada petani meliputi pengetahuan, sikap, umur, masa kerja, pendidikan, pengawasan, pelatihan, dukungan, dan ketersediaan APD. Kata Kunci: Alat Pelindung Diri, APD, Kepatuhan, Petani